Exploration des pratiques de littératie en milieu familial et portrait démolinguistique d’élèves immigrants allophones nouvellement arrivés en situation de grand retard scolaire au Québec - Armand, Françoise; Gagné, Judith; De Koninck, Zita; Dutil, Catherine (Canadian Journal of Applied Linguistics, 2005)
As in most metropolises throughout the world, the influx of migrants has completely altered the look of schools in Quebec’s larger cities. Among the immigrant children recently registered in Quebec schools, a number had not previously received or completed regular schooling. The case of pupils in a delayed schooling situation is still a misunderstood reality: we know little about them, especially their literacy development. However, in Quebec, successful reading acquisition in French as a second language is a sine qua non condition to school achievement and, therefore, represents a major challenge for these learners. It thus seems important to gather data on delayed schooling learners so as to enhance our knowledge of them and of their parents, and better understand home literacy practices and other demolinguistic variables related to success in reading acquisition. The objectives of this exploratory study are to trace a demolinguistic portrait of the parents and the children in such a situation; to present a synthesis of the declared literacy practices of these immigrant pupils; and to complete the portrait by exposing, in an exploratory fashion, the expectations and the perceptions of these parents towards schooling. The study was based on a questionnaire which was completed by 10 parents of pupils in a delayed school situation, and by 72 parents of regular allophone pupils recently registered in the primary or secondary level.